2021
DOI: 10.3389/fmolb.2021.636647
|View full text |Cite
|
Sign up to set email alerts
|

A Multifunctional Peptide From Bacillus Fermented Soybean for Effective Inhibition of SARS-CoV-2 S1 Receptor Binding Domain and Modulation of Toll Like Receptor 4: A Molecular Docking Study

Abstract: Fermented soybean products are traditionally consumed and popular in many Asian countries and the northeastern part of India. To search for potential agents for the interruption of the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Spike glycoprotein 1 (S1) and human angiotensin-converting enzyme 2 (ACE2) receptor interactions, the in silico antiviral prospective of peptides identified from the proteome of kinema was investigated. Soybean was fermented using Bacillus licheniformis KN1G, Bacillus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 71 publications
0
16
0
2
Order By: Relevance
“…The P13human TLR4/myeloid differentiation factor (MDF2) complex is known for its critical role in the cytokine storm based on in silico analysis. These results suggest that ALPEE-VIQHTFNLKSQ has greater potential to be applied as an antiviral agent and used as a prophylaxis agent against viral diseases, including coronavirus disease 2019 and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection (Table 1) [108]. As the production of various antiviral peptides is dependent on the culture conditions of species as well as the strain, further studies of selected peptides using molecular docking systems are needed to demonstrate that the peptide interacts with the active residues of SARS-CoV-2 spike glycoprotein (S1) receptor-binding domain and the human TLR4/MDF2 complex.…”
Section: Antimicrobial and Antiviral Effectsmentioning
confidence: 99%
“…The P13human TLR4/myeloid differentiation factor (MDF2) complex is known for its critical role in the cytokine storm based on in silico analysis. These results suggest that ALPEE-VIQHTFNLKSQ has greater potential to be applied as an antiviral agent and used as a prophylaxis agent against viral diseases, including coronavirus disease 2019 and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection (Table 1) [108]. As the production of various antiviral peptides is dependent on the culture conditions of species as well as the strain, further studies of selected peptides using molecular docking systems are needed to demonstrate that the peptide interacts with the active residues of SARS-CoV-2 spike glycoprotein (S1) receptor-binding domain and the human TLR4/MDF2 complex.…”
Section: Antimicrobial and Antiviral Effectsmentioning
confidence: 99%
“…Molecular docking mechanism confirmed that the purified peptide PTR is an excellent inhibitor for the main protease of SARS-CoV2. Similarly, Padhi et al 29 reported that fermented soybean peptides showed perfect interaction with the main protease of SARS-CoV-2. Another study reported by Wong peptides, which contain bulky side group amino acid-like arginine, proline, tryptophan, tyrosine lysine, showed higher inhibitory activity, 15 which could be the reason PTR showed the higher main protease inhibitory activity.…”
Section: Molecular Docking Studymentioning
confidence: 90%
“…Bioactive peptides (BP) are those peptides having a biological function or a specific protein fragments that have a positive impact on body functions or conditions and may influence health [58,60]. BP plays a major role in human health by improving the digestive, endocrine, cardiovascular, immune, and nervous systems [11,61,62]. Edible insects have peptides which are naturally present as well as those produced on enzymatic hydrolysis of insect protein.…”
Section: Production Of Bioactive Peptides Using Proteasesmentioning
confidence: 99%